Stargazer - Gray, Claudia (New York : HarperTeen, 2009)
Teenage vampire Bianca finds herself the target when evil wraiths attack her boarding school, Evernight Academy.
Keywords: Vampires -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Horror stories